Usefulness and Limits of DOAC Removal Agents Based on Activated Charcoal in Thrombophilia Testing: Literature Review and Expert Proposals - Jourdi, Georges; Flaujac, Claire; De Maistre, Emmanuel; Gendron, Nicolas; Eschwège, Valérie; Mauge, Laetitia; on behalf of the French Society on Thrombosis Haemostasis (Thrombosis and Haemostasis, 2025)
Although inherited and acquired thrombophilia screening should ideally be performed outside of any direct oral anticoagulant (DOAC) therapy, it is sometimes performed in patients who are anticoagulated. However, DOACs have been shown to interfere with many hemostasis tests, with a risk of false-positive/negative results in lupus anticoagulant testing and overestimation of natural coagulation inhibitor levels, which may lead to misdiagnosis. Devices have been developed to overcome DOAC interference but their role in thrombophilia testing is not clearly established. In this comprehensive review, we provide an in-depth overview of the literature on the impact of DOACs on thrombophilia assays, including lupus anticoagulant testing, antithrombin, protein C, and protein S assessment. DOACs can interfere with the results of thrombophilia testing even at low concentrations; therefore information on current or recently discontinued anticoagulant treatment should be provided when prescribing thrombophilia testing. Data on the usefulness of the most used DOAC removal systems based on activated charcoal to circumvent DOAC interference are heterogeneous. They are summarized in this critical review. Although activated charcoal could be useful to remove DOACs from plasma prior to thrombophilia testing, it may not be completely effective, particularly with apixaban. Hence, and in the light of the available literature, we provide 22 practical proposals for reliable thrombophilia testing and accurate result interpretation in samples from patients receiving DOACs and treated in vitro with activated charcoal.
Keywords: direct oral anticoagulant; lupus anticoagulant; antithrombin; protein C; protein S